REVITALISASI PENDIDIKAN ISLAM BERBASIS KETELADANAN SULTAN AL-FATIH DI ERA MODERN - Ngatmin Abbas; Dudi Budi Astoko; M. Fatchurrohman (STKIP Pesisir Selatan, 2026)
Objective: The abstract is important because many journal readers read the abstract first to determine whether the entire article is worth reading. The abstract is a shortened version of the paper and should contain all the information the reader needs to determine: (1) what the purpose of the study was; (2) how the study was conducted; (3) what results were obtained; (4) and Novelty. Methods: The abstract is important because many journal readers read the abstract first to determine whether the entire article is worth reading. Results: The abstract is important because many journal readers read the abstract first to determine whether the entire article is worth reading. The abstract is a shortened version of the paper and should contain all the information the reader needs to determine: (1) what the purpose of the study was; (2) how the study was conducted; (3) what results were obtained; (4) and Novelty. Novelty: The abstract is important because many journal readers read the abstract first to determine whether the entire article is worth reading. The abstract is a shortened version of the paper and should contain all the information the reader needs to determine: (1) what the purpose of the study was; (2) how the study was conducted; (3) what results were obtained; (4) and Novelty. The abstract can be 150 – 250 words.